CHOICE OF THE THEME OF MONOGRAPH IN THE BACHELOR IN LAW - Gonçalves, Jonas Rodrigo (Revista Coleta Científica, 2021)
Choosing the topic of a Course Paper in a law degree is complex. It starts with the following problem: “Is choosing the topic of a Course Paper in a degree in Law a great challenge?”. As a hypothesis, it is believed so. The general objective of this manuscript is to investigate whether there is complexity for a university graduate in the Bachelor of Laws in choosing the topic of Course Work. The specific objectives are: to present internal and external factors that influence the choice of theme for a Law Course Paper; suggest a way to make the definition of the theme simpler and more objective; list subjects and contents separated by areas of Law, based on the study of course textbooks. This study is relevant for students and faculty advisors in the Law course, for legal science and for society. It is a theoretical and documentary research lasting three months.